The Folklore Detective: Forensic Narrative Analysis - Lattanzi Shutika, Debra (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2019)
This essay will provide an overview of the work of narrative criminologists and how that scholarship overlaps with the work of narrative folklore. Criminologists have long relied on stories as an essential aspect of their work, but “narrative criminology” only entered scholarly conversations of criminologists in the 2000s. Drawing on the case of the West Virginia co-ed murders in 1970, I will demonstrate how narrative criminologists and folklorists might work together to create a new methodology that I’m calling forensic narrative analysis.